KEMAMPUAN MENULIS TEKS LAPORAN HASILOBSERVASI SISWA KELAS x sma darul ma’arif triguna padang - Suarti, Ayu; Khairani, Zuraida; Chan, Dwi Mutia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
This research is motivated by: First, students did not understand the structure of the text of the observation report correctly and had difficulty distinguishing each structure of the text of the observation report. Second, students find it difficult to express the results of their thoughts to convey them in writing. Third, students find it difficult to put together complete words. This type of research is quantitative research with descriptive methods. The data for this research are the scores from the performance test for writing text report observations of class X students at SMA Darul Maarif Triguna Padang. Based on the results of the research, it was concluded as follows: First, the ability to write report texts based on observations of class X student at SMA Darul Maarif Triguna Padang  for indicators general statement is classified as good (B) with an average of 81.12 in the range 76-85% on a scale of 10. Second, the ability to write report texts based on observations of class X student at SMA Darul Maarif Triguna Padang for indicator section description is classified as  very good (BS) with an average of 90 in the range 86-95% on a scale of 10. Third, the ability to write report texts based on observations of class X student at SMA Darul Maarif Triguna Padang for indicator description of benefits is classified as more than enough (LdC) with an average of 66,67 in the range 66-75% on a scale of 10. Fourth, the ability to write report texts based on observations of class X student at SMA Darul Maarif Triguna Padang for overall it is classified as good (B) with an average of 80.371 in the range of 76-85% on a scale of 10.